The FBI and religion : faith and national security before and after 9/11 - Johnson, Sylvester A., 1972-; Weitzman, Steven, 1965- (Oakland, California : University of California Press, 2017)
"...the first to examine the fraught relationship between the Federal Bureau of Investigation and religious groups in the United States in the past century. Encompassing religious organizations from established institutions to extremist groups and covering a period that includes the World Wars, the Cold War, the Civil Rights movement, and 9/11, this book tackles questions of importance for understanding American religion, the history of law enforcement, and the future of religious liberty"--Back cover.
Introduction "true faith and allegiance" : religion and the FBI / Sylvester A. Johnson and Steven Weitzman -- American religion and the rise of internal security : a prologue / Kathryn Gin Lum and Lerone A. Martin -- "If God be for you, who can be against you?" : persecution and vindication of the Church of God in Christ during World War I / Theodore Kornweibel, Jr. -- The FBI and the Moorish Science Temple of America, 1926-1960 / Sylvester A. Johnson -- J. Edgar Hoover, the FBI, and the religious cold war / Dianne Kirby -- Apostles of deceit : ecumenism, fundamentalism, surveillance, and the contested loyalties of Protestant clergy during the Cold War / Michael J. McVicar -- The FBI and the Catholic Church / Regin Schmidt -- Hoover's Judeo-Christians : Jews, religion, and Communism in the Cold War / Sarah Imhoff -- Policing public morality : Hoover's FBI, obscenity, and homosexuality / Douglas M. Charles -- The FBI and the Nation of Islam / Karl Evanzz -- Dreams and shadows : Martin Luther King Jr., the FBI, and the Southern Christian Leadership Conference / Sylvester A. Johnson -- A vast infiltration : Mormonism and the FBI / Matthew Bowman -- The FBI's "cult war" against the Branch Davidians / Catherine Wessinger -- The FBI and American Muslims after September 11 / Michael Barkun -- Policing Kashmiri Brooklyn / Junaid Rana -- Allies against Armageddon? : the FBI and the academic study of religion / Steven Weitzman.
Includes bibliographical references and index.
Keywords: United States. -- Federal Bureau of Investigation; Law enforcement -- United States -- Religious aspects; Religion and law -- United States